The Role of Indigenous Beliefs in Contemporary Indonesian Society: Resilience or Adaptation? - Azzahra Nurul; Mutiara Syahira; Qamarul Hadi; Arthit Kwanrattanakul (Studies in Indonesian Contemporary Religiosity and Modern World, 2025)
This paper explores the role of indigenous belief systems in contemporary Indonesia, focusing on how these traditions continue to exist amidst the pressures of modernization, religious conversion, and state policies. By examining case studies from indigenous communities such as the Dayak, Toraja, and Balinese, the research investigates how these groups are negotiating their cultural and religious practices within a predominantly Muslim society. The paper assesses whether indigenous belief systems are adapting by incorporating elements of global religion and modern technologies, or if they are resisting such pressures in favor of preserving their spiritual autonomy. Through fieldwork and ethnographic analysis, this study contributes to the understanding of the resilience of indigenous beliefs in Indonesia, highlighting how these communities are navigating the complex dynamics of modernization, religious pluralism, and state-sponsored religious policies. The paper also explores the role of indigenous spirituality in broader societal debates about nationalism, cultural preservation, and human rights. This research contributes to the fields of anthropology, religious studies, and cultural preservation by offering an in-depth analysis of how indigenous religions persist and adapt in a rapidly changing modern world.